The Cambridge handbook of successful aging - Fernández-Ballesteros, Rocío; Benetos, Athanase; Robine, Jean-Marie (Cambridge handbooks in psychology, 2019)
Recent studies show that more people than ever before are reaching old age in better health and enjoying that health for a longer time. This Handbook outlines the latest discoveries in the study of aging from bio-medicine, psychology, and socio-demography. It treats the study of aging as a multidisciplinary scientific subject, since it requires the interplay of broad disciplines, while offering high motivation, positive attitudes, and behaviors for aging well, and lifestyle changes that will help people to stay healthier across life span and in old age. Written by leading scholars from various academic disciplines, the chapters delve into the most topical aspects of aging today - including biological mechanisms of aging, aging with health, active and productive aging, aging with satisfaction, aging with respect, and aging with dignity. Aimed at health professionals as well as general readers, this Cambridge Handbook offers a new, positive approach to later life